PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE DAN MEDIA VIDEO DAKWAH UNTUK MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF PERSUASIF BERMUATAN PENDIDIKAN KARAKTER PADA SISWA KELAS X MA - Riana Hastiti; Evi Chamalah; Leli Nisfi Setiana (PBSI, FKIP UNISSULA, Semarang, 2017)
The purpose of this research is (1) to describe the improvement of writing skill of persuasive writing of class X student of MA Al Anwar Mranggen Demak afterapplied Think Pair Share model and video media of da’wah with charactereducation, (2) to describe the improvement of learning attitude of grade X MA AlAnwar Mranggen Demak after following the writing of persuasive paragraph withThink Pair Share model and video media da’wah with character education, and(3) to describe the increase of learning motivation of grade X MA Al AnwarMranggen Demak after following lesson writing persuasive paragraph with ThinkPair Share model and video media of da’wah Charged character education. Thisresearch is a quantitative and qualitative research. Quantitative research that is in the form of value analysis from test result writing persuasive paragraph.Qualitative research in the form of data analysis from nontes result throughobservation, questionnaire, interview, and documentation. Based on the result of research that has been done, it can be seen that the skills of students of class X MA Al Anwar Mranggen Demak in writing persuasive paragraphs have increased. This can be known through the writing of a persuasive paragraph in each cycle. In prasiklus students get a grade point average of 43,5. In the first cycle the average grade of the students increased to 61,17. In cycle II the students get the average grade of 64,83 and on the third cycle the average grade of the students to 78. It proves that the writing of the persuasive paragraph of the students has increased in cycle I, cycle II, and cycle III.